Standardization of thermal process parameters of canned tender jackfruit - Babu, Pritty S; K P, Sudheer (Journal of Postharvest Technology, 2019)
Value addition of jackfruit (Artocarpus heterophyllus L.) is a key strategy to promote its trade. Many of the value added products of jackfruit are either sugar or oil based and not suitable for daily consumption. An alternative would be the consumption of tender jackfruit as vegetable. Thermal processing appeared to be a promising preservation method to ensure year round availability of tender jackfruit for vegetable purpose. The identification of suitable time-temperature combination is an essential pre-requisite for thermal processing. The present study focus on standardisation of time-temperature required for thermal processing of canned tender jackfruit. A total of four treatments related to pasteurisation (TP) and sterilisation (TS) namely, TP1 (90oC, F=8), TP2 (90oC, F=10), TP3 (100oC, F=8), TP4 (100oC, F=10), TS1 (110oC, F0=1), TS2 (110oC, F0=2), TS3 (121oC, F0=1) and TS4 (121oC, F0=2) were examined under two factorial completely randomised design framework. Duration of thermal processing was computed from heat penetration curve. Based on the results of both microbiological and quality attributes (texture, colour, pH, total soluble solids and crude fibre content), the study advocates the use of pasteurisation at 90oC for 19 minutes (TP2) or sterilisation at 121oC for 38 minutes (TS3) for thermal processing of canned tender jackfruit.